Ayurvedic Management of Vatik Kasa in Era of Covid 19- A Case Series (International Journal of Ayurveda and Pharma Research, 2022)
Majority of the patients having cough (Kasa) is the presentation of respiratory disease. In general, air pollution; smoking and improper food habits are the triggering factors, which enhance this disease. Since the time 2nd wave of COVID 19 has gone the patients these days are coming with the major complaints of severe itching in the throat along with dry cough. Kasa is Kapha-Vata dominant disorder having 5 types, among which the pattern of cough relates to most of the symptoms of Vatik Kasa. The drugs like Vasavaleha and Chandramruta rasa helps to alleviate the vitiated Kapha Vata Dosha along with Haritaki as Anulomna and Abhyanga with Sarshapa taila mixed with Saindhava lavan, and Vashpa swedana on Uraha Pradesh. The major symptoms of Vatika Kasa subsided within 3 days and rest of the symptoms got cured in 10 days. Aim: Management of Vatik Kasa by Ayurvedic treatment modalities. Methodology: The study was conducted on three patients having symptoms of Vatik Kasa. In this case series, 3 patients were treated with local Abhayanga and Swedana, Haritiki, Vasavaleha and Chandramruta rasa and for 10 days. Conclusion: The use of Vasavaleha and Chandramruta rasa Muhurmuha along with local Abhyanga and Swedana showed significant improvement in the symptoms of the patients. Improvement was quite quick and highly significant on the symptoms of Vatika Kasa.